Acute Hypoxia Induces Enkephalin Production and Release in an Adrenergic Cell Line Model of Neonatal Chromaffin Cell Responses to Hypoxic Stress - Calero, Alexa; Villanueva, Hazel; Giri, Priyadarshani; Tischler, Arthur S.; Powers, James F.; Evinger, Marian (American Journal of Perinatology, 2018)
Objective Prior to maturation of the human sympathetic nervous system, the neonatal adrenal medulla senses and responds to hypoxia. In addition to catecholamine release, the adrenal medulla synthesizes and stores opioid peptides, notably enkephalin (ENK). However, it is not known whether acute hypoxia evokes adrenal ENK production and release, as seen in the central nervous system (CNS). We hypothesize that acute hypoxia stimulates synthesis and release of ENK in chromaffin cells.Study Design Cultures of adrenergic mouse pheochromocytoma cells (MPC) 10/9/96CR were incubated in 10% oxygen (O2) at intervals of up to 60 minutes. ENK content and release were measured by Met-ENK enzyme-linked immunosorbent assay (ELISA). ENK messenger ribonucleic acid (mRNA) was analyzed by quantitative reverse-transcriptase polymerase chain reaction (PCR).Results Incubation of MPC 10/9 cells in 10% O2 evoked rapid release of epinephrine and of Met-ENK which increased approximately twofold in 15 minutes. Reduced [O2] also induced an overall increase (14%) in cellular ENK peptide content within 60 minutes. Acute hypoxia-stimulated release of Met-ENK was accompanied by increased mRNAENK expression in MPC 10/9s, a cell culture model of adrenergic chromaffin cells.Conclusion We speculate that the ability of reduced [O2] to evoke ENK release from chromaffin cells may influence blood pressure regulation and heart contractility, thereby providing an adaptive survival advantage during neonatal asphyxia.
Keywords: enkephalin; catecholamines; adrenal medulla; epinephrine